Penyuluhan Hukum Terhadap Hak Pengelolahan Wisata Pantai Untuk Mendukung Pendapatan Adat Di Negeri Eti Kabupaten Seram Bagian Barat Menurut Perspektif Kesejahteraan Masyarakat - Saija, Ronald; Pariela, Marselo Valentino Geovani; Sihite, Sri Rumada (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Management Rights originating from State Land and Ulayat Land. Management rights originating from State land are granted to Central Government Agencies, Regional Governments, State-Owned Enterprises/Regional-Owned Legal Entities, Land Bank Agencies or legal entities appointed by the Central Government. Meanwhile, management rights originating from Ulayat Land are assigned to customary law communities. However, in managing tourism itself, it is necessary to pay attention to the impact and intersection of customs or culture of the community around the tourist destination area.Purposes of Devotion: The purpose of writing this article is to provide legal understanding and education to the people of Negeri Eti, West Seram Regency regarding the use of beach tourism to improve the welfare of the people of the Traditional Country. Method of Devotion: Legal education activities in Eti country are carried out using a panel discussion method where the presenters present the material in turns, then followed by questions and answers between the presenters and the community.Results of the Devotion: Developing tourism potential in an area certainly requires information, physical factors and a good coastal environment which includes accessibility, supporting facilities and infrastructure. With the existence of Village Regulation Number 1 of 2022 concerning Management of Land, Coastal and Marine Natural Resources in Eti Village, West Seram District, Maluku Province, Eti Village can implement it to provide welfare for coastal indigenous communities in the future.